Pandemic Influenza and Canada's Children - Joanne M Langley (Canadian Journal of Infectious Diseases and Medical Microbiology)
Paediatricians and others who care for children are familiar with the regular epidemic of respiratory illnesses that accompanies the annual visit of influenza virus each winter. In recent years, media interest in new strains of influenza has generated much public interest in, and often anxiety about, the threat of an influenza pandemic. Around the world, local, regional and national jurisdictions are engaged in contingency planning for the inevitable surge of illness, shortage of human and material resources, and societal disruption that is expected to accompany this event. In the present Paediatric Infectious Disease Note, we review briefly the potential implications of pandemic influenza for Canadian children, and the actions that paediatricians and others who care for children can take to prepare for this inevitable event.